The Effect Of Auditor Competence And Auditor Independence On Audit Quality With Auditor Ethics As A Moderating Variable - Giany Nur Aprilia; Nurul Hidayah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Financial statements that have been audited by a public accountant are more trustworthy than unaudited or unaudited financial statements. However, in recent years the quality of audits produced by public accountants has been under scrutiny by the public because there are differences in the auditor's opinion with the actual condition of the company. Auditor competence, auditor independence and auditor ethics have an important role in ensuring audit quality. This research is a quantitative study, using a survey method using purposive sampling with the respondent criteria for each KAP being 1 auditor. Data was collected using a questionnaire instrument which was measured using a Likert scale. The population of this study were auditors working at the Public Accounting Firm (KAP) in South Jakarta with active status at the OJK, totaling 76 KAPs and receiving 55 respondents to a questionnaire. The data analysis used was using the partial least squares (PLS) with the help of the SmartPLS program. The results of data analysis prove that: (1) auditor competence has a significant positive effect on audit quality with an original sample estimate of 0.369, a statistic of 3.594 and a significance <0.05, (2) auditor independence has a significant positive effect on audit quality with an original sample estimate value of 0.567, t-statistic 3.191 and significance <0.05, (3) auditor ethics can positively moderate the influence of auditor competence on audit quality with an original sample estimate value of 0.288, t-statistic 2.445 and significance <0.05, (4) and auditor ethics not can moderate the influence of auditor independence on audit quality with an original sample estimate value of -0.251, a t-statistic of 1.584 and a significance > 0.05. The practical implication of this research is to produce high audit quality, auditors must improve the competence, independence and ethics of their auditors so that the resulting audit report can be the basis for making the right decision.